Fikih Konservasi Laut: Relevansi Fiqh al-BÄ«Ê¼ah di Wilayah Pesisir Lamongan - Mufid, Moh (Fakultas Syariah IAIN Purwokerto, 2018)
This paper aims to reconstruct fishing jurisprudence in Lamongan regency in an eco-sharia perspective. Eco-sharia is a religious value that serves as a tool of social control for coastal communities in utilizing sustainable fisheries resources. Marine conservation efforts are a guarantee for the protection of marine resources in order to remain protected and sustainable. Fishing jurisprudence needs to be formulated to provide eco-sharia insight for fishermen about environmentally friendly fishing and in accordance with religious values. Fishing jurisprudence will be constructed based on fishery conservation practices in Lamongan regency as one of the coastal areas of Pantura (north coast of Java) that has been designated as a â€œminapolitanâ€ fishery town. The implications of the reconstruction of fishing jurisprudence are expected to build a culture conscious of the marine environment and synergize the economic and ecological aspects as a culture for the fishermen community.